Analysis of Musculoskeletal Disorders (MSDs) of Pharmaceutical Workers - Mariawati, Ade Sri; Adiatmika, I Putu Gede; Adiputra, Nyoman; Surata, I Wayan (Journal of A Sustainable Global South; Vol 5 No 2 (2021): August 2021DO - 10.24843/jsgs.2021.v05.i02.p01, 2021)
Pharmaceutical work activities have a high repetition level with a work attitude of standing for 8 hours potentially causing musculoskeletal complaints, which can occur despite the normal work posture. This study aims to determine musculoskeletal disorders (MSDs) and the level of MSDs based on what categories are felt, the level of complaints, the level of frequency, and the severity. The research design using the questionnaire Nordic Body Map. The study was conducted in 17 pharmacies on 54 pharmaceutical workers. The results obtained by MSDs complaints based on what categories of pain statements obtained (43.2%), cramps (16.13%), aches (53.5%). The category of complaint level obtained statement rather sick (55.9%), sick (33.5%). The category of frequency level obtained by the statement that occurs 1 to 2 times per week (56.5%), and every day (10.6%). And the severity category states that the perceived complaint is still working (49.06%) and uncomfortable (47.1%). Index Terms — Muscle Fatigue, MSDs, Nordic Body Map, Pharmacist Assistant